2022
DOI: 10.3390/ijerph19052610
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Self-Sampling for Primary Cervical Cancer Screening in Under-Screened Women in Hong Kong during the COVID-19 Pandemic

Abstract: The aim of this study was to assess the effectiveness of HPV self-sampling for cervical cancer screening and the best means of service delivery, with a specific focus on under-screened women, particularly during the COVID-19 pandemic. Using three arms of service delivery (social media, school outreach and underserved outreach), we recruited under-screened women aged 30–65 years from two population groups: the general public and specific underserved communities, from whom self-sampled specimens and optional cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
(23 reference statements)
0
11
1
Order By: Relevance
“… 10 , 11 , 23 - 27 , 29 - 37 , 39 - 47 , 49 , 50 , 54 , 57 - 60 , 63 - 65 , 68 - 71 , 74 Studies reported high satisfaction of self-collection among women, 10 , 11 , 30 , 36 , 42 , 43 , 50 , 58 , 62 , 63 , 65 , 68 , 70 that women were willing to perform self-collection again, 10 , 11 , 23 , 27 , 29 - 31 , 35 , 41 , 49 , 57 , 58 , 60 , 68 , 69 and to recommend self-collection to others. 10 , 11 , 27 , 29 , 30 , 32 , 49 , 50 , 68 Self-collection was commonly described as easy, 10 , 11 , 26 , 29 , 30 , 33 - 36 , 39 - 41 , 43 , 50 ...…”
Section: Resultsmentioning
confidence: 99%
“… 10 , 11 , 23 - 27 , 29 - 37 , 39 - 47 , 49 , 50 , 54 , 57 - 60 , 63 - 65 , 68 - 71 , 74 Studies reported high satisfaction of self-collection among women, 10 , 11 , 30 , 36 , 42 , 43 , 50 , 58 , 62 , 63 , 65 , 68 , 70 that women were willing to perform self-collection again, 10 , 11 , 23 , 27 , 29 - 31 , 35 , 41 , 49 , 57 , 58 , 60 , 68 , 69 and to recommend self-collection to others. 10 , 11 , 27 , 29 , 30 , 32 , 49 , 50 , 68 Self-collection was commonly described as easy, 10 , 11 , 26 , 29 , 30 , 33 - 36 , 39 - 41 , 43 , 50 ...…”
Section: Resultsmentioning
confidence: 99%
“…Ngu et al likewise reported that the concordance for HPV detection between self-sampled and clinician-sampled specimens was 90.2% (95% con dence interval [CI]: 85.1-93.8%; Cohen's kappa 0.59 [95% CI: 0.42-0.75]) in Hong Kong. These researchers conclude that HPV self-sampling is an effective method for cervical cancer screening and can be considered an effective screening option, especially in women who are reluctant or unable to attend regular screenings [11].…”
Section: Discussionmentioning
confidence: 96%
“…We have seen some examples of acceleration of HPV self-sampling programming in diverse settings, largely thanks to the disruption of routine services caused by COVID-19. Innovative strategies that had been successful in demonstration projects include community-based screening and mail-in HPV self-collection to maintain accessibility of cervical cancer screening services ( Woo et al, 2022 ; Castle et al, 2011 ; Ejegod et al, 2022 ; Winer et al, 2019 ; Ngu et al, 2022 ).…”
Section: Recommendations For Future Actionmentioning
confidence: 99%